Epigraphic Scheme of the Bestowed Mughal Mosque of Maryam Zamani at Lahore - Abbas, Masooma; Jamal, Syeda Roohi (Journal of Development and Social Sciences, 2024)
The objective of the research is to explore the motive behind building this Mosque through its calligraphic inscriptions that either it was an act of reverence and bestowment or an endowment project, to serve public faith, by the royal patron. Epigraphic schemes of Mughal Mosques reflect the thought behind the construction of their Mosques, such is the case of Maryam Zamani Mosque of 1614 at Lahore built during the reign of Jahangir in the name of his mother Maryam Zamani. This Panchmukhī Masjid is profusely decorated with non-figurative motifs in fresco among which calligraphic scripts Nast’alīq, Thuluth and Ṭughrā compositions have their own significance. Most of the scholarship related to Maryam Zamani Mosque is limited to descriptive information related to its locality and plan of the Mosque. The research deploys Feldman’s art historical research method by qualitatively analyzing the collected data from on-site visits, photography, study of the inscriptions and related scholarly data. The novel aspect of studying its epigraphic scheme, comprised of Quranic and poetic inscriptions, to explore its construction as a bestowment Imperial project is of prodigious significance which will add valuable knowledge to the existing sparse information on Mughal calligraphy at Lahore. This research also conserves the faded vanishing epigraphy which can be used for restoring the calligraphic specimens.